2018
DOI: 10.1007/s00382-018-4125-3
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of model spatial resolution on the vertical structure of convection in the tropics

Abstract: This study examined the impacts of model horizontal resolution on vertical structures of convection in the tropics by performing sensitivity experiments with the NCAR CESM1. It was found that contributions to the total precipitation between top-heavy and bottom-heavy convection are different among various resolutions. A coarser resolution tends to produce a greater contribution from top-heavy convection and, as a result, stronger precipitation in the western Pacific ITCZ; while there is less contribution from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…Due to their fine grid spacing, important processes such as large‐scale condensation, land‐sea interaction, and topographical forcing are better resolved in high‐resolution GCMs (Boyle & Klein, ; Lau & Ploshay, ; Harris et al, ). Recent studies further emphasized that the regional convective structure and precipitation change are very sensitive to the model horizontal resolution (Bui et al, ; Liu, Yu, & Chen, ). HIRAM model has been previously used effectively to simulate aerosol's direct radiative and circulation impacts (Bangalath & Stenchikov, ; Dogar, ; Dogar & Sato, ; Dogar & Shahid, ; Dogar, Stenchikov, et al, ; Osipov et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their fine grid spacing, important processes such as large‐scale condensation, land‐sea interaction, and topographical forcing are better resolved in high‐resolution GCMs (Boyle & Klein, ; Lau & Ploshay, ; Harris et al, ). Recent studies further emphasized that the regional convective structure and precipitation change are very sensitive to the model horizontal resolution (Bui et al, ; Liu, Yu, & Chen, ). HIRAM model has been previously used effectively to simulate aerosol's direct radiative and circulation impacts (Bangalath & Stenchikov, ; Dogar, ; Dogar & Sato, ; Dogar & Shahid, ; Dogar, Stenchikov, et al, ; Osipov et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This study extends the model sensitivity experiments of Bui et al (2019a) to answer the following questions: (1) How does model spatial resolution impact the statistical behavior of convective spectrum across the tropics? (2) How does the associated CRE change with convective spectrum in both SW and longwave (LW)?…”
Section: Introductionmentioning
confidence: 85%
“…For example, a few sensitivity tests were conducted by Labbouz et al (2018) to evaluate the effect of different physical processes that might be crucial in simulating the convection structure. By running the National Center for Atmospheric Research (NCAR) Community Atmospheric Model version 5 (CAM5) using different spatial resolutions, Bui et al (2019a) recently showed that a higher spatial resolution tends to produce more shallow convection, whereas a coarser one tends to generate less shallow convection. These results have critical implications for explaining different precipitation distributions in the tropics and understanding how the precipitation pattern might change in the future under a warmer climate (Bui et al 2019b;Chen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, this explanation is not suitable to what is shown in the equatorial central‐western Pacific in Figure c, where the intermodel relationship between T * and normalΔωrtm is reversed. Other factors, such as the intermodel differences in the sensitivity of ω ′ to T * (Huang et al ., ), the vertical structure of convection in response to surface warming (Chen et al ., ; Bui et al ., ), may be relevant, which is worth further study in the future. Owing to the dominant role of normalΔωrtm in the intermodel uncertainty in Δ P ′, the regression patterns of Δ P ′ onto both Δ T * and T * are very similar to the regression patterns of normalΔωrtm onto Δ T * and T * , respectively.…”
Section: Sources Of Intermodel Uncertainty In δP′mentioning
confidence: 99%